Verifying Diagnosis of Refractory Celiac Disease With Urine Gluten Immunogenic Peptides as Biomarker - Moreno, María de Lourdes; Sánchez-Muñoz, Diego; Sanders, David; Rodríguez-Herrera, Alfonso; Sousa, Carolina (Frontiers in Medicine, 2021)
Refractory celiac disease (RCD) involves T-lymphocyte activation despite supposed absence of gluten exposure. Assessing dietary adherence is the cornerstone of RCD diagnosis, but available diagnostic tools fail to monitor gluten-free diet (GFD). A recently acknowledged GFD biomarker is gluten immunogenic peptides (GIP) in urine. This study assessed urine GIP to verify whether RCD patients could be reclassified as “exposed to gluten”. Three out of four RCD patients had at least two positive-GIP urine samples in a follow-up of 3 months, demonstrating gluten exposure. Urine GIP may enable the accurate RCD verification and decrease overuse of immunosuppressants, increasing cost-effectiveness.